ANALYZING THE EFFECTS OF OMNICHANNEL STRATEGY AND CUSTOMER EXPERIENCE ON LOYALTY: THE MEDIATING ROLE OF CUSTOMER SATISFACTION - Sarah Madaniah; Arlina Nurbaity Lubis; Endang Sulistya Rini (RADJA PUBLIKA, 2025)
The beauty industry has experienced significant and rapid growth in recent years. However, this growth has not been reflected in Sociolla's revenue, which has shown fluctuations and a downward trend. In its annual report, Sociolla stated that it has implemented an omnichannel system to enhance customer experience. Surprisingly, this system has become the least utilized shopping channel among its consumers. Previous studies have also presented mixed results regarding the implementation of omnichannel strategies and customer management. This phenomenon has gained increasing attention from both academics and industry practitioners due to the growing challenges in delivering effective customer service. This study aims to examine and analyze the influence of omnichannel system usage and customer experience on customer loyalty through customer satisfaction at Sociolla Sun Plaza Medan. The research adopts an associative approach with quantitative data. The population consists of Sociolla customers at Sun Plaza Medan, whose total number is unknown. 210 respondents were selected using purposive sampling, with criteria including having made at least three purchases at Sociolla Sun Plaza Medan and having used multiple shopping channels. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4.0. The results indicate that the use of the omnichannel system has a positive but insignificant effect on both customer satisfaction and loyalty. In contrast, customer experience has a positive and significant effect on both satisfaction and loyalty. Regarding indirect relationships, customer satisfaction does not mediate the effect of omnichannel system usage on customer loyalty. However, customer satisfaction does mediate the relationship between customer experience and loyalty at Sociolla.